Cultural Heritage Diplomacy as Turkish Soft Power: The Impact of Ottoman-Era Building Restoration on the Tourism Economy in Albania - Syihabuddin Syihabuddin; Nur Fatwa; Nova Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The paradigm shift of power in International Relations positions cultural heritage diplomacy as a strategic soft power instrument. Through the Turkish Cooperation and Coordination Agency (TİKA), Türkiye funds the restoration of Ottoman-era buildings in the Balkans to strengthen its geopolitical influence. This study aims to analyze how Türkiye's cultural diplomacy strategy contributes to the tourism economy in Albania. Employing a qualitative approach with a document analysis method, this research evaluates academic literature, institutional reports, statistical data, and public discourse in mass media using reflexive thematic analysis. The findings reveal a pragmatic symbiosis between Türkiye's ambitions and Albania's economy. Although Albania's tourism is predominantly driven by nature and coastal attractions, the restoration of historical buildings by Türkiye is utilized by Albania to diversify its cultural tourism sector. A geopolitical paradox emerges: Eastern-nuanced assets funded by Türkiye paradoxically become tourist commodities whose primary market consists of European citizens (accounting for 95% of the 11.7 million tourists in 2024). Conversely, new construction projects such as the Namazgâh Mosque trigger domestic ambivalence, as the